Soil surfactant use on athletic field infield surfaces. Issue 1 (12th January 2021) - Thoms, Adam W.; Lindsey, Alex J.; Pease, Ben W.
Abstract: Infield skins are best managed by deep and slow additions of water, but time between games limits these applications. A two‐year study was conducted on a collegiate club softball infield skin to evaluate if applications of soil surfactants could extend soil moisture levels in infields. Seven soil surfactants treatments (Magnus at 15.9 L ha −1 and Magnus 2x at 31.8 L ha −1, Vivax at 15.9 L ha −1, Cascade at 25.5 L ha −1 and Cascade 2x at 50.9 L ha −1, Vivax Tab at 3.3 L water m −2, and Precision EZ Tab at 3.3 L water m −2 ), as well as a nontreated control (NTC) were applied. Linear regression analysis for soil moisture readings resulted in the Vivax Tab having greatest water loss (−0.44% h −1 ) along with the NTC (−0.41% h −1 ) in 2018, however no differences were present in 2019. Contrast statements compared the NTC to the soil surfactants and only Magnus 2x offered a lower water loss over time than NTC. Magnus 2x provided a harder surface than the NTC immediately after watering, and a lower surface hardness than all other treatments after 4 h. In 2019, only Vivax Tabs and Cascade 2x did not have lower surface hardness values than the NTC immediately after watering, and by 8 h after watering only Vivax had a lower surface hardness than NTC. Treatment affects were not consistent from year to year, but it appears increased rates may be needed to change soil moisture and hardness levels for any duration. Future research should focus on increased rates of soil surfactants for infield skins on different skin materials.